Identifikasi Kandungan Senyawa Aktif Antibakteri Ekstrak Bawang Putih dalam Menghambat Pertumbuhan Bakteri Cutibacterium acnes Penyebab Acne Vulgaris - Aprianti, Shervia Dwi; Sibero, Hendra Tarigan; Aditya, Muhammad; Himayani, Rani (Medula, 2024)
Introduction: The cases of antibiotic resistance in the treatment of acne vulgaris have been steadily increasing. A study conducted by the Dermatology Clinic of Hanyang University Hospital, South Korea, showed an increase in antibiotic resistance cases in the management of acne vulgaris, with resistance rates of 30% for clindamycin and 26.7% for erythromycin. One adjunctive therapy believed to be a breakthrough in anticipating the increase in antibiotic resistance causing acne vulgaris is the use of garlic extract. This study aims to conduct antibacterial phytochemical screening of garlic extract in inhibiting the growth of Cutibacterium acnes. Methods: The antibacterial active compounds in garlic plants were identified through phytochemical screening. Meanwhile, the antibacterial test was conducted using the well diffusion method with garlic extract concentrations of 25%, 50%, 75%, and 100%. Clindamycin was used as the positive control. Results: The phytochemical screening results of garlic extract in this study revealed the presence of flavonoids, alkaloids, tannins, phenols, and terpenoids. In the antibacterial test using the well diffusion method, the largest inhibition zone was observed with clindamycin treatment, while the smallest inhibition zone diameter was recorded with 25% garlic extract concentration. Discussion: The active antibacterial compounds found in garlic extract, including flavonoids, alkaloids, tannins, phenols, and terpenoids, have been proven to inhibit the growth of Cutibacterium acnes, as indicated by the formation of inhibition zone diameters in the antibacterial test.